2020
DOI: 10.2147/ndt.s235416
|View full text |Cite
|
Sign up to set email alerts
|

<p>Social Anxiety Disorder Among Undergraduate Students of Hawassa University, College of Medicine and Health Sciences, Ethiopia</p>

Abstract: Introduction: Social anxiety disorder (SAD), also called social phobia, is an uncontrollable fear of social situations, which involve fear of observation or making contact with strangers. So, helping individuals with social anxiety, which is among the factors affecting mental health, can significantly influence a students' mental health and prevent other problems. Objective: The study aimed at assessing the magnitude of SAD and its determinants among undergraduate students of Hawassa University, College of Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 20 publications
2
15
0
3
Order By: Relevance
“…Studies have shown that 10% of college students in the United Kingdom suffer from SA ( Russell and Shaw, 2009 ). Further, 30% of newcomers suffered from SA in Australia ( Wilson, 2005 ), while the percentage of SA among students in medical specialties in Iraq, Kingdom of Saudi Arabia, and India was 28.3, 29.8, and 30.5%, respectively ( Ahmad et al, 2017 ; Hakami et al, 2017 ; Jarallah et al, 2017 ; Dsouza et al, 2019 ; Reta et al, 2020 ). SA has a significant negative impact on interpersonal relationships, work, and academic performance, such as increasing the risk of dropping out of school, reducing work efficiency, and affecting the quality of life ( Aderka et al, 2012 ; Jacobson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that 10% of college students in the United Kingdom suffer from SA ( Russell and Shaw, 2009 ). Further, 30% of newcomers suffered from SA in Australia ( Wilson, 2005 ), while the percentage of SA among students in medical specialties in Iraq, Kingdom of Saudi Arabia, and India was 28.3, 29.8, and 30.5%, respectively ( Ahmad et al, 2017 ; Hakami et al, 2017 ; Jarallah et al, 2017 ; Dsouza et al, 2019 ; Reta et al, 2020 ). SA has a significant negative impact on interpersonal relationships, work, and academic performance, such as increasing the risk of dropping out of school, reducing work efficiency, and affecting the quality of life ( Aderka et al, 2012 ; Jacobson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ren and Li (2020) found that PE has a significant impact on the SA of left-behind children in rural Chinese areas. Moreover, some previously mentioned researchers from the United Kingdom, Austria, Iraq, Saudi Arabia, India, and Ethiopia conducted studies in their own countries ( Wilson, 2005 ; Russell and Shaw, 2009 ; Ahmad et al, 2017 ; Hakami et al, 2017 ; Jarallah et al, 2017 ; Dsouza et al, 2019 ; Reta et al, 2020 ). However, few studies have examined the relationship between PE, IA, and SA in a group of Chinese college students.…”
Section: Introductionmentioning
confidence: 99%
“…13 In Ethiopia, research conducted on prevalence of social phobia among high school students in Woldia, Gondar and Hawassa was 27.5%, 31.2%, 32.8%. [14][15][16] Factors have shown to have an association include being the first or only child, 17 medical science faculties, 18,19 being female, younger age, religion, marital status (unmarried), the presence psychiatric illness, having a positive family history of mental disorder had a significant role for development of social phobia. 16,20 Evidence showed that social phobia was associated with substance use, 21 low socioeconomic status, unemployment, low level of education, and social support.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, the prevalence of social anxiety disorder was found to be 63% among persons aged 12-17 years and it was significantly associated with female gender, low educational status, sexual victimization, and experience of peer victimization [7]. Another two different studies conducted on social anxiety disorder among university students in Ethiopia revealed a 31.2% [8] and 32.8% [9] prevalence. The comorbidity of SAD with schizophrenia is common, and it is the most frequent type of anxiety disorder in schizophrenia patients [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%